Mn-doped NiWO4 quantum dots with superior electrochemical and conductivity performance for energy storage application. (1st December 2022) - Chatterjee, Mahasweta; Saha, Samik; Chatterjee, Tuli; Das, Sachindranath; Pradhan, Swapan Kumar
Abstract: Monoclinic amorphous Ni1-x Mnx WO4 (x = 0.00, 0.02) compounds have been successfully synthesized by hydrothermal technique for achieving better capacitive and conductive performances. Different characterization techniques like X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), ultraviolet-visible (UV–Vis) and photoluminescence (PL) spectroscopy have been employed to investigate their structural, microstructural, and optical properties. Mn-ion incorporation in the NiWO4 lattice reduces the particle size of the sample to ∼4.5 nm, compared to the pure undoped NiWO4 sample (∼18 nm), confirmed from the transmission electron microscopy image and Brunauer–Emmett–Teller analyses (BET). Tauc plot of Ni0.98 Mn0.02 WO4 sample exhibits a significant increase in bandgap energy, compared to pure undoped NiWO4 sample due to the quantum confinement effect. The electrochemical performance of electrodes made with these materials has been revealed by cyclic voltammetry (CV), galvanostatic charge-discharge (GCD) properties and electrochemical impedance spectroscopy (EIS). Moreover, the addition of 2 % Mn in NiWO4 causes an increase in specific surface area (117.390 m 2 /g) due to the reduced particle size of the material, resulting in excellent specific capacitance of 463 F g −1 at 0.5 A g −1 current density. The detailed charge storage mechanism for the improvement of conductivity and electrochemical performance of the Mn-doped NiWO4 has been revealed in different studies. An asymmetric supercapacitor device (ASC) has been fabricated using Mn-doped NiWO4 electrode material as positive electrode. The device shows superior cyclic stability upto 5000 cycles, can retain 88.4 % of its initial value. Graphical abstract: Unlabelled Image Highlights: Ni.98 Mn.02 WO4 quantum dots (size∼4 nm) successfully designed in low temp annealing. Addition of 2 % Mn enhances surface area, specific capacitance of the NiWO4 lattice. Doping provides higher conductivity and many active sites. Mn doped NiWO4 quantum dots with its unique characteristics are reported first time.